STUDY OF MICROALBUMINURIA AS A CARDIOMETABOLIC RISK FACTOR IN TYPE 2 DIABETES MELLITUS: A CROSS-SECTIONAL STUDY. - Sahu, Sugatha; Satpathy, Bidyut Prava; Behera, Pushpanjali (Student's Journal of Health Research Africa, 2024)
Background The rising occurrence of type 2 diabetes mellitus (T2DM) presents considerable health hazards, particularly concerning heart-related complications. The presence of microalbuminuria acts as an important indicator for the early identification of vascular injury and cardiometabolic risks in individuals with T2DM, emphasizing the necessity for regular screening. Aims This work aims to assess the prevalence of microalbuminuria in individuals with type 2 diabetes mellitus in patients residing in Odisha. Methods This cross-sectional study took place for over 2.5 years at MKCG Medical College and Hospital, involving 110 patients diagnosed with T2DM. Participants were recruited from the outpatient and inpatient departments of General Medicine and Endocrinology, after obtaining informed consent. Comprehensive demographic and clinical data were collected, alongside laboratory assessments for microalbuminuria using an immunoassay method. Results The study comprised 65 males and 45 females, with an average age of 57.07 years. Microalbuminuria was found in 24 of 27 patients (88.89%) with diabetes for 11 years or more (p < 0.05). Additionally, 25 of 41 patients (61%) with elevated HbA1C levels had microalbuminuria. Mean fasting blood sugar was significantly higher in the microalbuminuria group (142.83 ± 37.32 mg/dL vs. 127.85 ± 31.36 mg/dL). Conclusion Microalbuminuria is significantly associated with the duration of diabetes, poor glycemic control, dyslipidemia, and renal dysfunction in patients with type 2 diabetes mellitus. Recommendation: Microalbuminuria is a marker of vascular disease and can be used to support further therapy directed at this complication. For the stated reasons, microalbuminuria testing is recommended.